Mechanism to generate a two-dimensional electron gas at the surface of the charge-ordered semiconductor BaBiO3 - Vildosola, Veronica Laura (2013)
In this Letter, we find by means of first-principles calculations a new physical mechanism to generate a two-dimensional electron gas, namely, the breaking of charge ordering at the surface of a charge-ordered semiconductor due to the incomplete oxygen environment of the surface ions. The emergence of the 2D gas is independent of the presence of oxygen vacancies or polar discontinuities; this is a self-doping effect. This mechanism might apply to many charge-ordered systems, in particular, we study the case of BaBiO 3(001). Our calculations show that the outer layer of the Bi-terminated simulated surface turns more cubiclike and metallic while the inner layers remain in the insulating monoclinic state that the system present in the bulk form. On the other hand, the metallization does not occur for the Ba termination, a fact that makes this system appealing for nanostructuring. Finally, in view of the bulk properties of this material under doping, this particular finding sets another possible route for future exploration: the potential scenario of 2D superconductivity at the BaBiO3 surface.